MENTORING STUDENTS OF SDN 34 SIGUNTUR TUA TO MAINTAIN CLEANLINESS AND THE ENVIRONMENT IN THE NEW NORMAL ERA, PESISIR SELATAN REGENCY, WEST SUMATRA - Irwan, Irwan; Melia, Yenni; Siska, Felia; Elvawati, Elvawati; Sulkaisi, Neffi; Kartika Sandra, Heru (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Education is able to answer the problems of students and solve the problems faced today. Awareness to protect the environment is very important to be understood by the younger generation, starting from the world of education, especially in the New Normal era. The focus of this study analyzes the application and assistance to students to maintain cleanliness and the school environment in the new normal era. The service method uses direct observation and direct application to students of SDN 34 Siguntur Tua, by carrying out several stages, namely (a) procedures and data collection for program implementation; (b) building cooperative relationships between partners and the education office at the district and provincial levels; (c) evaluation design. The results of the service show that students are enthusiastic in practicing a clean lifestyle in the new norm era. The conclusion is that the actions taken by students work together in community service at school, this shows a sense of caring to maintain the environment at school.